PENGUJIAN OTOMATIS SISTEM INFORMASI INDO TOWING DENGAN KATALON STUDIO - Mutiara, Mutiara; Qomariyah, Nurul; Widyawati, Dewi Kania (Program Studi Teknologi Rekayasa Internet, Politeknik Negeri Lampung, 2024)
The development of web-based and mobile information systems that support various aspects of human work has become the main focus in the current technological era. The importance of automation testing in ensuring software quality is becoming increasingly profound. The quality of these systems is critical to supporting successful business operations. Automation testing using the STLC method and equivalence partitioning technique is applied to ensure the quality of the Indo Towing system. The testing tool used is Katalon Studio, which facilitates the implementation of automated testing with efficiency. Thus, this study emphasizes the importance of automation testing as a crucial step in software development. The results of the implementation of automation testing using Katalon Studio were successfully carried out according to the information system function without any bugs being found in the system. Tests carried out automatically using Katalon Studio can be concluded that the system is running well.